ANALISIS STRATEGI BISNIS PADA TOKO BUKU GRAMEDIA DUTA PLAZA DI KOTA DENPASAR - Fitriandari, Mahayanti; Sukaatmadja, I Putu Gde; Giantari, I Gusti Ayu Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.03.TAHUN 2015, 2015)
The purpose of this research is to analyze : external factors in order to identify opportunities and threats of Gramedia Duta Plaza Bookstore; internal factors in order to identify strengths and weaknesses of Gramedia Duta Plaza Bookstore; business position of  Gramedia Duta Plaza Bookstore, and; the most relevant strategies used in business for Gramedia Duta Plaza Bookstore in the future. To answer the aims of this study, a research was conducted with nine people on the key management as main respondents, and seven external respondents for confirmation. SWOT analysis method  is used to find external factors and internal factors of the company. The analytical technique used was IE Matrix. The results showed that an adequate strategy to be implemented by the company in the future is a strategy to grow and develop (growth and build). The implication of the research object in the future is to bring the attention of management to focusing on the strategies facing "discount war” made vigorously by competitors, maximizing the company's strategic location to optimize the limited space, creating an independent creative promotion to answer the centralized promotion system, and evaluating the procurement system by supplying best seller products, and products required by consumers.
Keywords: business strategy, SWOT, internal-external matrix